Self-esteem and estimation of surrounding people in adolescence - Grigorenko-Prigoda, Е.А. (ХНУ імені В.Н. Каразіна, 2012)
The article deals with self-esteem of adolescents and its influence on their estimation of surrounding people. The types of attitude of adolescents to themselves and to the surrounding people are considered.
Статья посвящена самооценке подростков и ее влиянию на их оценивание окружающих людей. Рассматриваются типы отношения подростков к себе и к окружающим людям.
Keywords: adolescents; attitude; estimation; relationships; self-esteem